2003
DOI: 10.1074/jbc.m210877200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor-dependent and -independent Cell-signaling Pathways Originating from the Urokinase Receptor

Abstract: Urokinase-type plasminogen activator (uPA) and vitronectin activate cell-signaling pathways by binding to the uPA receptor (uPAR). Because uPAR is glycosylphosphatidylinositol-anchored, the signaling receptor is most likely a uPAR-containing multiprotein complex. This complex may be heterogeneous within a single cell and among different cell types. The goal of this study was to elucidate the role of the EGF receptor (EGFR) as a component of the uPAR-signaling machinery. uPA activated extracellular signal-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 50 publications
7
122
0
Order By: Relevance
“…Further, up-regulation of uPAR expression by Bcl2 in hypoxia was mediated by SP1 DNA binding activity through ERK signaling pathway (43). Jo, et al (44) have also shown that, in the absence of EGFR, an alternate pathway links uPAR to ERK. However, this pathway is silenced by EGFR expression, hence indicating the involvement of uPAR in cell motility.…”
Section: Figmentioning
confidence: 99%
“…Further, up-regulation of uPAR expression by Bcl2 in hypoxia was mediated by SP1 DNA binding activity through ERK signaling pathway (43). Jo, et al (44) have also shown that, in the absence of EGFR, an alternate pathway links uPAR to ERK. However, this pathway is silenced by EGFR expression, hence indicating the involvement of uPAR in cell motility.…”
Section: Figmentioning
confidence: 99%
“…Binding of ligands to LRP1, in Schwann cells, activates Rac1; however, in fibroblasts, LRP1 inhibits Rac1 activation by decreasing the cell surface abundance of uPAR (28,29,38). The indirect pathway, in which LRP1 regulates Rac1 downstream of uPAR is active only when cells are cultured on VN.…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts that are plated on VN, LRP1 inhibits Rac1 activation downstream of the urokinase receptor (uPAR) by facilitating uPAR endocytosis (29,38). Because our studies were performed with Schwann cells cultured on FN and not VN, regulation of uPAR did not contribute to the effects of LRP1 on Rac1 activation.…”
Section: Lrp1 Regulates Rac1 In An Extracellularmentioning
confidence: 98%
“…In HEp3, COS-7, and MCF-7 cells, EGFR tyrosine kinase antagonists block uPA-induced ERK activation (20,26). The EGFR co-immunoprecipitates with uPAR and with ␤1 integrin (20); however, the mechanism by which the EGFR supports uPAR-initiated ERK activation remains unclear.…”
mentioning
confidence: 99%